Social Support as a Key Factor in Understanding Social Anxiety Among Generation Z - Hasbullah, An Nisaa Zahra; Dawanti, Rizki (Universitas Mercu Buana, 2025)
Social anxiety is a common problem among Generation Z, characterized by fear of negative evaluation, difficulty in social interactions, and a tendency to avoid social situations. Social support is believed to help reduce social anxiety by providing a sense of security, acceptance, and emotional support. This study aims to examine the effect of social support on social anxiety among Generation Z in JABODETABEK. Using a quantitative approach with simple linear regression analysis, this study involved 150 respondents selected through incidental sampling. This study used the Social Anxiety Scale for Adolescents (SAS-A) and the Multidimensional Scale of Perceived Social Support (MSPSS) as measuring instruments. The findings of the study showed that social support had a significant negative effect on social anxiety. Among the various sources of support, support from significant others had the strongest impact, at 16.8%, compared to support from friends and family. These findings emphasize the role of significant others in preventing and reducing social anxiety in Generation Z.